Determination of Quality Characteristics of Advanced Chickpea Genotypes - Ömer SÖZEN; Gözde Nur PEKER (ISPEC Journal of Agricultural Sciences)
The research carried out between 2021 and 2022 to determine the quality parameters of some advanced chickpea genotypes in Kırşehir ecological conditions was established on the trial plots of Kırşehir Ahi Evran University Agricultural Research and Application Area. In the study, 40 chickpea genotypes, including 35 local chickpea genotypes selected by pure line selection method and 5 chickpea cultivars registered by Agricultural Research Institutes in our country, were used. The study, which was carried out for two years, was established in an augmented trial design with 4 replications. During the research, water uptake capacity (g seed-1), water uptake index (%), swelling capacity (ml seed-1), swelling index (%), coat ratio (%), and protein ratio (%) data of 6 quality characteristics of chickpea genotypes were revealed. According to the results of the analysis of variance, statistically significant or very important differences were determined between the chickpea genotypes in terms of all the quality parameters. In the study carried out, the highest protein rate was determined in the N-21 chickpea genotype at 24.99%, while the lowest protein yield was determined in the N-36 chickpea genotype at 19.34%.